Eco-Friendly Nanocellulose Filter Paper: A Potential for Removal of Dye from Textile Wastewater - ISHAK, NOOR IZZATUL HUSNA; Abdul Hamid, Nor Hazren (Progress in Engineering Application and Technology, 2023)
Textile wastewater has now become one of the largest producers of wastewater as the demand for that product increase. The various process involved the usage of various types of chemical substances and dye agents that can pollute the water once it were discharged into a water body such as a river or lake. Therefore, the high concentration of the dyes will cause harm towards the surrounding environment including humans, animals and the ecosystem. There are vary method of treatment such as filtration and adsorption in treating wastewater. The objectives of this study are to investigate the performance of the filter paper towards textile wastewater as well as to determine the optimum dosage of filter paper. Different dosage and pH is used in order to find the best performance of filter paper through filtration. Then, it is significant in distinguishing and investigating the functional group present in CNFs filter paper via Fourier Transform Infrared Spectroscopy (FTIR). From the result obtained, the optimum pH and dosage removal of colour from textile wastewater samples are found to be at pH 9 and dosage of 60. This show that the use of filter paper in removing the dye effluent in textile wastewater is applicable. However, some improvements need to be taken in order to create a better efficiency of filter paper performance.